BS EN IEC 62321-8. Determination of certain substances in electrotechnical products. Part 8. Phthalates in polymers by gas chromatography-mass spectrometry (GC-MS), gas chromatography-mass spectrometry using a pyrolyzer/thermal desorption accessory (Py-TD-GC-MS) (26th January 2023) - British Standards Institution,
No abstract available